Application of the Erbium: YAG laser in all-ceramic crown removal and related nursing management (Er: YAG 激光治疗仪在去除全瓷冠粘接中的应用与护理) - DONG Yang (董阳) (中西医结合护理)
This paper summarized the practice of the Erbium: YAG laser in all-ceramic crown removal and related nursing management. Key issues of nursing included: Preoperative comprehensive assessment, informed consent, instrument and laser equipment inspection; Intraoperative monitoring of vital signs, assisting in parameter setting and safety protection; postoperative guidance on oral care, follow-up appointments, immediate cleaning and disinfection of the equipment and recoding; daily implementation of equipment maintenance, operation training and use of norms. Strict implementation of perioperative nursing procedure is a guarantee of patient safety and improving nursing satisfaction. (本文总结Er: YAG激光去除全瓷冠粘接治疗中的护理流程和经验。Er: YAG 激光治疗护理操作需贯穿术前、术中和术后全过程。术前全面评估、知情同意、器械及激光设备检查; 术中监测生命体征, 协助参数设定与安全防护; 术后指导口腔护理、预约复诊, 设备即刻清洁消毒并记录; 日常落实设备维护、操作培训及使用规范。通过严格执行围术期护理操作, 有效保障患者治疗安全, 提高护理满意度。)